Interaction of two pulses in defocusing nonlinear Schrodinger equation - Hassan, Torla; Tadjimuratov, Sadulla; Wahiddin, Mohamed Ridza; Regaa, Nassima; Umarov, Bakhram A. (IOP, 2013)
In this work we are using initial conditions in the form of two separated bright pulses with the rectangular shape to analyse the interaction of pulses in a defocusing Nonlinear Scrodinger Equation (NLSE). By exact solution of the direct scattering problem associated with the defocusing NLSE, we have obtained the expressions for long time behavior of the solution. Obtained results interpreted as a nonlinear interference of two pulses.